Manajemen Pembelajaran Al Quran Disekolah Dasar - Muhamad Nurois Amin Rois (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2022)
Abstract Reading the Qur'an for a Muslim is considered worship, therefore studying the Qur'an is also worship. Even some scholars argue that studying the Qur'an is obligatory. Because the Qur'an is the most basic guide for every Muslim. By studying the Qur'an, it is proven that Muslims are responsible for their holy book. Rasulullah SAW has encouraged us to study and teach the Qur'an to others. In the process of learning the Qur'an, good management is needed, so it is hoped that with good management it can clarify, make it easier to evaluate to achieve the expected target.